Pro VB 2010 and the .NET 4 Platform - Troelsen, Andrew; Agarwal, Vidya Vrat.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Be the first to understand .NET 4.0 and Visual Basic 2010. Pro VB 2010 and the .NET 4.0 Platform provides developers with a complete guide to the new technology, explaining the importance of all the key VB 2010 language features. This edition has been comprehensively revised and rewritten to make it accurately reflect the VB 10 language specification for the .NET 4.0 platform. You$1 (Bll find new chapters covering the important concepts of dynamic lookups, named and optional arguments, Parallel LINQ (PLINQ), improved COM interop, and variance for generics. The first edition of this book was released at the 2001 Tech-Ed conference in Atlanta, Georgia. At that time, the .NET platform was still a beta product, and in many ways, so was this book. This is not to say that the early editions of this text did not have merit$1 (Bafter all, the book was a 2002 Jolt Award finalist and it won the 2003 Referenceware Excellence Award. However, over the years that author Andrew Troelsen spent working with the common language runtime (CLR), he gained a much deeper understanding of the .NET platform and the subtleties of the VB programming language, and he feels that this sixth edition of the book is as close to a (3z(Bfinal release(3y (Bas he$1 (Bs come yet! If you$1 (Bre checking out this book for the first time, do understand that it$1 (Bs targeted at experienced software professionals and/or graduate students of computer science (so don$1 (Bt expect three chapters on iteration or decision constructs!). The mission of this text is to provide you with a rock-solid foundation in the VB programming language and the core aspects of the .NET platform (assemblies, remoting, Windows Forms, Web Forms, ADO.NET, XML web services, etc.). Once you digest the information presented in these 25 chapters, you$1 (Bll be in a perfect position to apply this knowledge to your specific programming assignments and explore the .NET universe on your own terms.s
Introducing VB 2010 -- Building Visual Basic 2010 Applications -- Core VB 2010 Programming Constructs, Part I -- Core VB 2010 Programming Constructs, Part II -- Defining Encapsulated Class Types -- Understanding Inheritance and Polymorphism -- Understanding Structured Exception Handling -- Understanding Object Lifetime -- Working with Interfaces -- Understanding Generics -- Delegates, Events, and Lambdas -- Advanced VB 2010 Language Features -- LINQ to Objects -- Configuring .NET Assemblies -- Type Reflection, Late Binding, and Attribute-Based Programming -- Processes, AppDomains, and Object Contexts -- Understanding CIL and the Role of Dynamic Assemblies -- Dynamic Types and the Dynamic Language Runtime -- Multithreaded and Parallel Programming -- File I/O and Object Serialization -- ADO.NET Part I: The Connected Layer -- ADO.NET Part II: The Disconnected Layer -- ADO.NET Part III: The Entity Framework -- Introducing LINQ to XML -- Introducing Windows Communication Foundation -- Introducing Windows Workflow Foundation 4.0 -- Introducing Windows Presentation Foundation and XAML -- Programming with WPF Controls -- WPF Graphics Rendering Services -- WPF Resources, Animations, and Styles -- WPF Control Templates and UserControls -- Building ASP.NET Web Pages -- ASP.NET Web Controls, Master Pages, and Themes -- ASP.NET State Management Techniques.
Keywords: Computer science; Computer Science; Computer Science, general